2019
DOI: 10.18632/aging.102205
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA, HOTAIRM1, promotes glioma malignancy by forming a ceRNA network

Abstract: Long non-coding RNAs play critical roles in tumorigenesis and the immune process. In this study, RNA sequencing data for 946 glioma samples from The Cancer Genome Atlas and the Chinese Glioma Genome Atlas databases were analyzed to evaluate the prognostic value and function of homeobox A transcript antisense RNA myeloid-specific (HOTAIRM)1. HOTAIRM1 expression was associated with clinical and molecular features of glioma: patients with high HOTAIRM1 expression were more likely to be classified as malignant cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…First, predicted binding of micro (mi)RNAs with the 10 lncRNAs were collected using the DIANA tools and LncBase Predicted v.2 ( https://www.microrna.gr/LncBase/ ). LncRNA/miRNA pairs and potential target genes of overlapping miRNAs were generated as described in our previous study [ 16 ]. Then, we identified miRNA-mRNA pairs by intersecting target genes with SRGs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, predicted binding of micro (mi)RNAs with the 10 lncRNAs were collected using the DIANA tools and LncBase Predicted v.2 ( https://www.microrna.gr/LncBase/ ). LncRNA/miRNA pairs and potential target genes of overlapping miRNAs were generated as described in our previous study [ 16 ]. Then, we identified miRNA-mRNA pairs by intersecting target genes with SRGs.…”
Section: Methodsmentioning
confidence: 99%
“…The RNA expressions of LINC01503, CD44, and OLIG2 were calculated by the 2 −ΔΔCt method and normalized to 18S mRNA expression. The procedure of protein isolation and western blotting was similar as that described in previous study [16]. The primary antibodies were as follows: CD44 (1:1000; Cell Signaling Technology, Boston, USA), OLIG2 (1:1000; Abcam, Cambridge, UK), β-actin (1:1000; Proteintech, Rosemont, IL, USA).…”
Section: Cell Transfection Qrt-pcr Protein Isolation and Western Blmentioning
confidence: 99%
“…In a glioma study, they report on the oncogenic role of maternally expressed 3 (MEG3) as a tumor suppressor lncRNA that is downregulated in gliomas [34] and nuclear paraspeckle assembly transcript 1 (NEAT1) on by competing for miR-let-7e and modulating the expression of signal transducer and activator of transcription 3 (STAT3) and NRAS proto-oncogene, GTPase (NRAS) [34,35]. The functions of lncRNAs as biomarkers and therapeutic targets in glioma are well reported [36][37][38]; Collectively, these findings showed that the interactions among lncRNAs, mRNA, and miRNA in ceRNA network implicate a potential role as tumor suppressive or oncogenic effects. However, data regarding their effects on OD and the 1p/19q codeletion remain limited.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a competing endogenous RNA (ceRNA) theory proposed recently, which suggests that non-coding RNAs and protein-coding RNAs work as ceRNAs through competing for miRNAs via shared miRNA recognition elements [14,15], has aroused wide concerns. Several ceRNA networks have been validated to play key functions in metastasis, proliferation, and apoptosis in human glioma cells [16,17]. The possible ceRNA networks in glioma and the mechanisms involved remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%